Characteristics of Methyl Ester Sulfonate (MES) Laundry Soap With The Addition of Salt and Ecoenzyme Additives: Karakteristik Deterjen Methil Ester Sulfonat (MES) Dengan Penambahan Garam dan Aditif Ecoenzyme - Rukmini, Piyantina; Indah Suryaningsih, Encis (Jurnal Kimia dan Rekayasa, 2025)
This research aims to determine the characteristics of deterjen with the surfactant Methyl Ester sulfonate (MES), the addition of Salt and ecoenzyme additives.  The research was carried out by reacting MES surfactant with Salt in concentrations of 0%, 5%, 10%, 20%, 30% and 40% of the weight of MES.  Ecoenzyme is added to the reactor when the temperature of the washing soap has reached 300C.  The reaction was carried out in 6 reactors and the parameters observed were pH, color, aroma, viscosity and density.  The research results showed that the reactor H4 with a Salt concentration of 20% of the MES weight showed results that were close to the quality of soap referred to by the government (SNI). AbstrakPenelitian ini bertujuan untuk mengetahui karakteristik deterjen dengan surfaktan Methil Ester sulfonat (MES), penambahan Garam dan aditif ecoenzim.  Penelitian dilakukan dengan mereaksikan surfaktan MES dengan Garam dalam konsentrasi 0%, 5%, 10%, 20%, 30%, dan 40% dari berat MES.  Ecoenzim ditambahkan ke dalam reaktor ketika suhu deterjen sudah mencapai 300C.  Reaksi dilakukan dalam 6 reaktor dan parameter yang diamati adalah pH, warna, aroma, viskositas, dan densitas.  Hasil penelitian menunjukkan bahwa pada reaktor H4 dengan konsentrasi Garam 20% dari berat MES menunjukkan hasil yang mendekati kualitas deterjen yang dirujuk oleh pemerintah (SNI).